COVID-19 Infection in a Patient with Common Variable Immunodeficiency: Experience with Favipiravir and Intravenous Immunoglobulin - (:unkn) unknown (My University, 2021)
Data regarding COVID-19 infection in patients with common variable immunodeficiency (CVID) are limited. Herein, we present a 28-year-old male patient with CVID admitted for intravenous immunoglobulin (IVIG) replacement with myalgia and a productive cough. A nasopharyngeal swab for the SARS CoV-2 polymerase chain reaction assay was positive. Chest computed tomography was consistent with COVID-19 pneumonia. The patient refused hospitalization and the applicable treatment for COVID-19. Although he was prescribed IVIG, he had a lapse in IVIG replacement due to supply problems. The patient was later brought to the emergency room due to the deterioration of his general condition with dyspnea, tachypnea, shortness of breath, cough, and fever five days after the initial presentation. He was treated with favipiravir and IVIG and had a positive outcome. Results of COVID-19 infection in CVID patients are diverse, possibly due to underlying genetic defects. Although our patient had an increased risk for severe disease due to CVID, a lapse in IVIG replacement, and obesity, he did not require intensive care or intubation. Further studies are needed to determine and develop treatment strategies for COVID-19 infection in patients diagnosed with CVID.